2008
DOI: 10.1057/9780230583702
|View full text |Cite
|
Sign up to set email alerts
|

Managing Flow

Abstract: This book is printed on paper suitable for recycling and made from fully managed and sustained forest sources. Logging, pulping and manufacturing processes are expected to conform to the environmental regulations of the country of origin.A catalogue record for this book is available from the British Library.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
16
0
9

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 233 publications
(25 citation statements)
references
References 2 publications
0
16
0
9
Order By: Relevance
“…The importance of organisational learning can be assessed from the research findings of Yeo (2005), which showed that learning promoted the performance of the organisation and facilitated the ability to sustain a competitive advantage in an uncertain and turbulent environment. Therefore, such organisational practices, which integrate and support learning, facilitate knowledge creation and sharing in the organisation, and lead to organisational innovation (Kontoghiorghes et al, 2005;Nonaka et al, 2008). Organisational learning entails the relationship of mental, spiritual, and physical energies of individuals.…”
Section: Learning Culturementioning
confidence: 99%
See 2 more Smart Citations
“…The importance of organisational learning can be assessed from the research findings of Yeo (2005), which showed that learning promoted the performance of the organisation and facilitated the ability to sustain a competitive advantage in an uncertain and turbulent environment. Therefore, such organisational practices, which integrate and support learning, facilitate knowledge creation and sharing in the organisation, and lead to organisational innovation (Kontoghiorghes et al, 2005;Nonaka et al, 2008). Organisational learning entails the relationship of mental, spiritual, and physical energies of individuals.…”
Section: Learning Culturementioning
confidence: 99%
“…The outcomes of organisational learning result in the creation of new knowledge as well as the individual development of mental and emotional behaviours (Gallagher et al, 2007). Organisational learning positively influences intellectual abilities and behaviours as well as social interactions among individuals and others in the organisation (Gallagher et al, 2007;Nonaka et al, 2008). Therefore, an organisational learning culture enhances the abilities of its individuals in terms of their behaviours and interactions associated with knowledge creation and knowledge sharing.…”
Section: Learning Culturementioning
confidence: 99%
See 1 more Smart Citation
“…A través de la espiral SECI, continuamente en movimiento, una empresa puede construir una capacidad de síntesis de conocimiento para perseguir tanto la creatividad como la eficiencia 46 , permitiendo que la creación de conocimiento pueda ser considerada como una síntesis de subjetividad y objetividad 47 . El interés de Nonaka era comprender cómo las empresas desarrollan productos y servicios innovadores aprovechando el poder de la creación de conocimiento.…”
unclassified
“…Sin embargo, el estudio profundo de los procesos organizativos lo lleva a reconocer la importancia de la agencia humana. En su obra maestra Managing Flow: A Process Theory of the Knowledge-Based Firm, presenta el proceso de dirección como un arte 48 , enfatizando el dinamismo en las organizaciones. Se observa en este trabajo una maduración de su pensamiento, y en especial la influencia de Aristóteles, puesta de manifiesto en el desarrollo de su liderazgo prudencial (phronetic leadership).…”
unclassified